HANDLING OF THE COVID-19 PANDEMIC BY THE GOVERNMENT IN VIEW FROM THE LEGAL PRODUCTS FORMED - Anggono, Bayu Dwi; Firdaus, Fahmi Ramadhan (Faculty of Law Universitas Trunojoyo Madura, 2023)
It's been almost a year since WHO declared Covid-19 to be a pandemic, this outbreak has infected almost all countries in the world and has affected various sectors. As a rule of law, Indonesia issued various legal products to deal with the impact of the Covid-19 Pandemic, especially from the health and economic sectors. This article will explain what legal products the government has formed to deal with pandemics and discuss the problems of legal products that apply in dealing with pandemics. The research method used in this study is Normative Juridical with a conceptual approach, statutory approach and comparative approach. This research will evaluate the legal products formed by the government because there are problems such as disharmony, in addition to another problem, namely the formation of laws formed by the House of Representatives together with the government which have no connection with the acceleration of the handling of the Covid-19 pandemic and are considered to be negligent. to the sense of crisis. One of the recommendations that can be implemented by the Government is to focus on establishing laws and regulations related to the handling of the Pandemic and evaluating the laws and regulations made in the context of handling the Pandemic in the past year.